Legal Position of Making a Deed of Sale and Purchase Binding Agreement (PPJB) That Does Not Comply with the Material Requirements - Abdon Longginus Michael Maku; Kusumo, Ayub Torry Satriyo; Saptanti, Noor (Siber International Journal of Advanced Law (SIJAL), 2025)
This study aims to determine how a deed is said to be in accordance with formal and material requirements and what are the legal consequences and legal status of a deed that does not comply with formal and material requirements. This study is a Normative Research with a Conceptual Approach. The legal materials used are primary legal materials in the form of the Civil Code, Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning the Position of Notary, secondary legal materials in the form of books, articles and related journals. While the data analysis method used is qualitative. The results of this study are that a Notarial deed including a Deed of Sale and Purchase Agreement must meet the requirements in Article 1320 of the Criminal Code and Article 38, Article 39, and Article 40 UUJN. The results of the second discussion are that a deed that does not meet the requirements of Article 1320 of the Criminal Code, Articles 38,39 and 40 UUJN has the same evidentiary force as a private deed.